PENGEMBANGAN MEDIA E-COMIC PADA PEMBELAJARAN IPAS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SD NEGERI SUKAREJO - Sihombing, Miduk Buah Cintya; Fransyaigu, Ronald; Ayudia, Inge (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the low learning interest of fifth-grade students at SDN Sukarejo in the science subject, which is identified as stemming from the lack of utilization of interactive and engaging digital-based learning media. To address this problem, this study aims to develop a learning media product in the form of an e-comic (electronic comic) and systematically test its level of validity, practicality, and effectiveness. The research method used is Research and Development (R&D) by adopting a structured ADDIE model, including the stages of Analysis (needs analysis), Design (concept design), Development (product development), Implementation (trial), and Evaluation (impact evaluation). Data collection was carried out comprehensively through observation, interviews, and questionnaires. The results of product validation by experts showed a